Virulence and antibiotic resistance genes in Campylobacter spp. in the Czech Republic - Bardoň, J; Pudová, V; Koláčková, I; Karpíšková, R; Röderová, M; Kolář, M (Epidemiologie, mikrobiologie, imunologie, 2017)
OBJECTIVE: Thermotolerant species of the genus Campy-lobacter are the important agents causing human foodborne infections throughout the world. The aims of this study were to evaluate the presence of nine putative virulence genes in Campylobacter spp. isolated from patients and from foods (poultry meat, pork liver), to determine the resistance of Campylobacter isolates to eight antibiotic agents and to detect four resistance genes.Matherial and methods: The presence of the virulence genes cdtA, cdtB, cdtC, virB11, ciaB, wlaN, iam, dnaJ and racR was detected by polymerase chain reaction (PCR) in 94 Campylobacter spp. isolates from humans and 123 campylobacters from foods. The phenotypic resistance to selected antimicrobial agents was tested with microdilution method in 82 human isolates and 91 food isolates. The isolates with antibiograms were tested for the presence of blaOXA-61, tet(O), aph-3-1 and cmeB genes by PCR with specific primers. RESULTS: In both human and food C. jejuni isolates the preva-lence of the studied virulence genes, especially dnaJ, racR, ciaB genes and the toxigenic genes cdtA, cdtB, cdtC, was considerably higher than in C. coli isolates. The only exception was the iam gene identified in only C. coli. The tested isolates of both C. jejuni and C. coli were highly resistant to quinolone antibiotics. Additionally, C. coli was also more resistant to erythromycin, streptomycin and, in case of isolates from pork liver, to tetracycline. High prevalence rates of genes encoding antibiotic resistance was noted for the blaOXA-61 and tet(O) genes in both Campylobacter species. CONCLUSIONS: The presented study is the first to assess the presence of genes for virulence and resistance to antibiotics in thermotolerant Campylobacter spp. isolated from humans and foods in the Czech Republic. The resistance of Campylobacter isolates to eight antibiotic agents was also assessed. The prevalence of genes responsible for virulence and resistance is rather varied in thermotolerant Campylobacter spp.
Keywords: Campylobacter Infections; Campylobacter; Virulence; bakteriální léková rezistence; Česká republika; kampylobakterové infekce; lidé; antibakteriální látky; Anti-Bacterial Agents; Czech Republic; Microbial Sensitivity Tests; Campylobacter - foodborne infections - virulence genes - resistance genes.; Drug Resistance, Bacterial; Humans; mikrobiální testy citlivosti; virulence